A NOVEL VALIDATED HEADSPACE GAS CHROMATOGRAPHY METHOD FOR THE SIMULTANEOUS QUANTIFICATION OF THREE ORGANIC VOLATILE IMPURITIES IN ENROFLOXACIN PURE AND PHARMACEUTICAL DOSAGE FORMS - KISHORE J, KRISHNA; RAO K, PRASADA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This article describes a novel, simple, and rapid gas chromatographic method for quantification of three organic volatile impurities (OVIs) present in enrofloxacin and its pharmaceutical dosage forms. Methods: As stationary phase using ZB-624 30 m×0.53 mm, 3.0 μ column with flame ionized detector at 250°C. The injector temperature is maintained at 180°C. The nitrogen gas was used as a carrier gas with a flow rate of 4.0 mL/min. The method involved a thermal gradient elution. The total run time is 21.14 min. Results: The retention time of three OVIs taken individually and in spiked standard solutions were determined. The retention times are 2.30 min for methanol, 7.07 min for 1-butanol, and 8.48 min for toluene, respectively. The % relative standard deviation for six injections should be not more than 10%. The % recovery ranges from 85 to 115%. The correlation coefficient (r2) for linearity is not <0.99. The limit of quantification was found to be 260 ppm for methanol, 101 ppm for 1-butanol, and 56 ppm for toluene. Furthermore, verified precision, ruggedness, robustness, solution stability, and pharmaceutical analysis. Conclusion: All the obtained results are found within the acceptable limits. The proposed method has been successfully applied for the quantification of OVIs present in enrofloxacin pure and its pharmaceutical dosage forms.